Association of serum magnesium level with small fiber neuropathy in patients with type 2 diabetes - Liu, Xiaoting; Hu, Jianzhang (Frontiers in Medicine, 2025)
PurposeWe aimed to investigate the association between serum magnesium (Mg) levels and small fiber neuropathy among patients with type 2 diabetes mellitus (T2DM).MethodsThis study retrospectively collected data from patients with T2DM. Patients were divided based on the quartiles of the serum concentrations of Mg. Corneal confocal microscopy (CCM) was employed to determine the morphological parameters of corneal nerve fibers, including corneal nerve fiber length (CNFL), fiber density (CNFD), and branch density (CNBD). Pearson correlation analysis and multiple linear regression analyses were conducted to investigate the association between the serum levels of Mg and the morphological parameters of corneal nerve fibers.ResultsIn total, 136 patients with T2DM were enrolled in this study. All morphological parameters of corneal nerve fibers increased with the increasing quartiles of serum Mg levels. Using Pearson correlation analysis, we found a significant and positive association between the serum levels of Mg and CNFL (r = 0.550, p < 0.001), CNFD (r = 0.432, p < 0.001), and CNBD (r = 0.425, p < 0.001). After adjusting for covariates, the serum levels of Mg remained positively correlated with CNFL (β = 0.495, p < 0.001), CNFD (β = 0.361, p < 0.001), and CNBD (β = 0.374, p < 0.001) in the fully adjusted model.ConclusionThe serum levels of Mg were positively and independently correlated with the morphological parameters of the corneal nerve among patients with T2DM. Serum Mg levels can serve as a potential biomarker for screening corneal small fiber neuropathy in patients with T2DM.